The Strategy of Civics Teachers in Instilling the Character of Love for the Motherland to Anticipate Radicalism Movements at Muhammadiyah 1 Vocational High School Palu - Indriani; Misnah; Herlina; Juraid Abdul Latief; Arif Firmansyah; Mahfud Gamar (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
Study this aim to know draft planting character love homeland in high school muhammadiyah 1 Palu , For know planting character love homeland in high school Muhammadiyah 1 Palu. For knowing obstacles And support instill love homeland in high school Muhammadiyah 1 Palu. Study This is a descriptive qualitative study. subject in study This is a teacher and student And withdrawal sample in study This using purposive sampling technique data collection technique using observation, interview And documentation . This study uses analysis techniques that are data reduction, data presentation, and verification/conclusion. The results of the study show the draft of planting the character of Love for the homeland at SMK Muhammadiyah 1 Palu done when beginning First student enter school, start from process test sufficient selection strict next with pattern habituation at school through flagship programs And school culture. planting character Love land water in learning through 3 stages that is planning, implementation and evaluation learning planting character Love land water in development self students , academic development like Olympic And extracurricular activity hizbul wathan, art dance , pencak silat , paskibraka , activities P5 ( project strengthening Pancasila student profile ) planting character Love land water in school culture ceremony flag And big national anniversary day, guard And conserve Indonesian culture, 5S culture , prayer noon And Salat Friday congregation in school. For obstacles And support on means And infrastructure, the obstacle just means in the every class it turns out after observation Still There is a class that means support values love land the water Still not enough like on the wall still class blank Not yet exist taking pictures of heroes